Pengaruh Konsumsi Edamame (Glycine Max L) dan Kurma (Phoenix Dactylifera L) terhadap Peningkatan Produksi ASI dalam Pencegahan Stunting - Nilda Yulita Siregar; Fransisca Noya noya (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2023)
One of the causes of stunting in toddlers is unbalanced food intake. Unbalanced food intake is included in exclusive breastfeeding that is not given for 6 months due to non-smooth breastfeeding. One way to facilitate the release of breast milk is to consume edamame and dates. The purpose of this study was to analyze the effect of consumption of Edamame (Glycine max L) and Dates (Phoenix dactylifera L) on increasing breast milk production in preventing stunting in the Mapane Health Center Work Area. The research design used was a quasi-experimental study, with a pretest-posttest control group design. Sampling in this study was purposive sampling with a total of 40 people. The data were processed and analyzed using a frequency distribution with a percentage measure and the Wilcoxon test. The results of this study showed that the mean weight of infants increased in the case group from 3.10 kg to 5.10 kg and in the control group from 3.05 to 4.50. The average body length of infants increased in the case group from 56.25 cm to 64.35 cm and in the control group from 53.40 cm to 60.5 cm. The results of the statistical test showed that there was a significant difference before and after the intervention, both the case group and the control group with p <0.05. The conclusion is that there is an effect of consuming edamame and dates on increasing breast milk production in preventing stunting in the Mapane Health Center Working Area.